PERAN STAKEHOLDERS DALAM PENGEMBANGAN WISATA ALAM JUMOG DI DESA WISATA BERJO, NGARGOYOSO, KABUPATEN KARANGANYAR - Chalysta Nurul Hidayah; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
The development and management of Jumog Nature Tourism still experience problems such as suboptimal BUMDes governance, limited involvement of tourism actors in decision making. This study aims to examine the role of stakeholders in the development of Jumog Nature Tourism in Berjo Village, Ngargoyoso District, Karanganyar Regency, using five dimensions of stakeholder roles, namely policy creator, coordinator, facilitator, implementor, and accelerator. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation of the Berjo Village Government, BUMDes Alam Berjo, Disparpora Karanganyar Regency, BENTUR Community, Business Actors, and also the community involved in tourism management. The results of the study indicate that the role of stakeholders in the development of Jumog Nature Tourism has been carried out collaboratively, but not yet fully optimal, seen from the five dimensions, namely policy creators who still experience obstacles in the form of unclear results of the formulated policies, then coordinators who show that there is still miscommunication and also lack of community involvement in communication, the role of facilitator actors who are lacking in providing support to target groups such as, lack of structured training, the role of implementor actors who are still overlapping and also the role of accelerators who are still lacking in providing encouragement to tourist destinations. Overall, the role of stakeholders in the development of Jumog Nature Tourism has a positive impact on the village but is still not optimal, this can be seen from the obstacles still faced by each stakeholder.